ANALISIS KUALITATIF KOMUNIKASI KADER POS YANDU DALAM IMPLEMENTASI PELAYANAN KEBIDANAN Di WILAYAH RT 03 RW 02 KELURAHAN MATTOANGIN KOTA MAKASSAR - Hafsah, Hafsah; Ibriani, Jumriana; Angraeni, Ningsi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Communication conducted by Posyandu cadres plays a crucial role in supporting the implementation of midwifery services at the community level, particularly in maternal and child health education programs. Effective communication contributes to improving health literacy, behavior, and community participation in Posyandu activities. This study aims to analyze the forms and quality of communication carried out by Posyandu cadres in implementing midwifery services in RT 03 RW 02, Mattoangin Subdistrict, Makassar City. This research employed a qualitative approach with a phenomenological design. Participants were selected using purposive sampling, consisting of five active cadres with at least two years of service experience, one supervisory midwife, and three mothers receiving services. Data were collected through in-depth interviews, participatory observation, and document review of Posyandu activities. The study setting was the local Posyandu facility routinely conducting monthly health services. Data analysis was performed using a thematic approach through data reduction, coding, categorization, interpretation, and source triangulation to ensure credibility. The findings indicate that cadre communication occurs through three dominant forms: interpersonal communication, small group communication, and health program–driven instructional communication. Interpersonal communication was the most frequently used method, particularly when delivering education related to exclusive breastfeeding, immunization, child nutrition, and growth monitoring. Supporting factors included strong social bonding and experience in community service. However, limitations were identified, including inadequate communication skills, unstructured message delivery, and limited use of digital educational media. In conclusion, communication by Posyandu cadres in midwifery service implementation is functioning but not yet optimal. Strengthening communication skills through digital-based health communication training and continuous mentoring by healthcare providers is recommended to enhance message effectiveness and improve the quality of midwifery service delivery at the Posyandu level. Keywords: health communication, Posyandu cadres, midwifery services, qualitative research, Makassar